Kesantunan Berbahasa Minangkabau dalam Tindak Tutur Direktif antara Anak dan Orang Tua di Ikur Koto Kecamatan Koto Tangah Padang - Vilayati, Ingvi Asri; Agustina, Agustina; Tressyalina, Tressyalina (Universitas Negeri Padang, 2012)
The purpose of this study were (1) describe the form of directive speech acts are used between children and parents at the hands of Ikur Koto Koto Padang District, (2) describes the strategy used in the recalled directive speech acts between children and parents in Ikur Koto Koto district hands of Padang, (3) describe the context of the situation tells that the use of strategies used in the directive speech acts between children and parents at the hands of Ikur Koto Koto Padang District. The data of this study is a form of directive speech act, speak strategies, and context of the situation said the children and parents at the hands of Ikur Koto Koto district. Source of research data is speech between children and parents who are natives of the area. Data was collected using the methods and techniques refer to the record and advanced engineering techniques as noted. The study's findings, namely directive speech acts between children and parents.